Regulations for organic agricultural production in Belize 2001 - Ministry of Agriculture, (Belize) (MoA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2017)
Recognises that the demand from consumers for organically produced agricultural products and foodstuffs is increasing, which has resulted in the creation of new market opportunities for Belizean organic agricultural products internationally and at the national level.